Clinical burden of obstructive hypertrophic cardiomyopathy in France - Philippe Charron; Carla Zema; François-Emery Cotté; Eléonore Herquelot; Taryn Krause; Florent Daydé; Jean-Noël Trochu (Frontiers in Cardiovascular Medicine)
BackgroundHypertrophic cardiomyopathy (HCM) can be genetic and occurs as obstructive and non-obstructive 21 subtypes. Little is known about the clinical burden of the obstructive subtype of HCM at a national 22 level, and how it may differ by New York Heart Association (NYHA) class. Therefore, this study 23 aimed to describe the clinical burden of patients hospitalized with obstructive HCM from a 24 nationwide study in France.MethodsThis retrospective, longitudinal, observational study was performed using data from the French National Health Data System. All adult patients (≥ 18 years old) with a hospitalization related to obstructive HCM [International Classification of Diseases, Tenth Revision (ICD-10) code I42.1], or at least one hospitalization with ICD-10 code I42.2 or I42.9 and at least one code for septal reduction therapy between 2012 and 2018 were included. Patients were followed up for a minimum of 1 year. NYHA class was assigned using an algorithm based on treatment and symptom codes. Treatment patterns and clinical outcomes by NYHA class over time were examined.ResultsOverall, 6,823 patients with obstructive HCM were included (54.7% male, mean [standard deviation (SD)] age 66.2 [16.7] years). At inclusion, the proportion of patients in NYHA classes I, II, III, and IV were 4%, 32%, 60%, and 4%, respectively. Over the follow-up [mean (SD) follow-up: 4.4 (2.5) years; cumulative patient follow-up: 30,021 patient-years], 73% of patients remained in the same NYHA class, 14% of patients worsened, and 13% improved. At inclusion, 22% of patients had no HCM-related treatment, 56% were receiving β-blockers, 12% calcium-channel blockers, and 11% a combination of both. The incidence of cardiovascular-related hospitalization was high (35,436 hospitalizations; 117,229 per 100,000 patient-years) and this risk increased with NYHA class (from 81,247 per 100,000 patient-years for NYHA class I/II patients to 140,790 per 100,000 patient-years for NYHA class III/IV patients, p < 0.0001).ConclusionsPatients with obstructive HCM are at high risk of death and cardiovascular outcomes, especially those in higher NYHA classes. Despite current therapeutics, the clinical burden of symptomatic obstructive HCM remains high, supporting the need for additional therapies.